Understanding Lifestyle Migration
XII, 249 p.
Keywords: This book draws on social theories to understand lifestyle migration as a social phenomenon. The chapters engage theoretically with themes and debates relevant to contemporary social science such as place and space, social stratification and power relations, production and consumption, individualism, dwelling and imagination.